Impact of Grants-in-aid on Collegiate Education - Narayana, M. R. (Education Policy Analysis Archives, 2001)
This article estimates the impact of grants-in-aid (GIA) and other variables on students' performance (in terms of pass percentages) in aided private degree colleges, using panel data from sample colleges in Bangalore district of Karnataka State (India) from 1991-92 to 1997-98. In addition, sensitivity of a reduction in GIA on the estimated pass percent of students in the individual colleges and feasibility of financing a reduction in GIA through proposed changes in students' fee are analysed. The results show that (a) the impact of GIA is positive and significant in all estimations; (b) the estimated pass percentage of students does vary remarkably, especially if GIA is reduced by 50 percent or more; and (c) the proposed fee revisions can finance a reduction in GIA to all colleges by about 12 percent. The framework of analysis and implications of empirical results above are of relevance for other regions in India as well as for other developing countries in assessing the policy impact of a reduction in public financing of higher education.